Foreign Bodies Adhered to the Structures of the Oral Cavity of Babies: Report of Two Cases - Ferraresso, Lucas Fernando Oliveira Tomáz; Hosida, Thayse Yumi; Souza, Vanuza Pinheiro; Silva, Cristiano Gama da; Morais, Leonardo Antônio de; Aguiar, Vitória Bittencourt de; Santana, Jéssica Silva; Delbem, Alberto Carlos Botazzo; Nagata, Mariana Emi; Cunha, Robson Frederico (ARCHIVES OF HEALTH INVESTIGATION, 2025)
Foreign bodies (FB) are characterized as unwanted objects that do not belong to the organism and can be lodged or adhered to the human body. This study aimed to report two clinical cases of FB adhered to different structures of the oral cavity in babies. Case 1: A 9-month-old male patient presented to the Faculty of Dentistry of UNESP, due to the presence of a painless lesion on the hard palate for approximately 15 days. Clinically, a yellowish, smooth, shiny, well-defined lesion with a hardened consistency and an erythematous halo at the edges was identified in the median region of the hard palate. Case 2: A 12- month-old female patient attended at the Baby Clinic of the State University of Londrina, due to the presence of a whitish cyst on the gum for approximately 7 days. Clinically, a whitish, smooth, shiny, well-defined lesion with a hardened consistency was identified in the posterior region of the gingival rim on the left side. In both cases, the approach taken was the removal of the FB. After the procedure, it was determined that the FB were, respectively, a silicone door impact protector and a plastic fragment from a toy. On clinical follow-up, the mucosa of the hard palate and gingival rim was observed to be normal. It is concluded that the presence of FB adhered to different locations of the oral cavity in babies represents situations that pose risks of aspiration or swallowing and physical examination allows for an immediate and accurate diagnosis.